The Malaysian Islamization Phenomenon: The Underlying Dynamics and Their Impact on Muslim Women - Olivier, Bob (Islam and Christian-Muslim relations, 2016)
Islamization in Malaysia, a Muslim-majority country with a large minority population (approximately 35%) of non-Muslims, has gathered pace over the last 40 years. The process has brought about profound changes in Malaysian society. Drawing upon data gathered through qualitative surveys, the article assesses the views of Malay Muslim women from ‘professional classes', or ‘elites' on the impact of Islamization on Muslim women in general and those from professional backgrounds in particular. The article also draws upon interviews conducted with Malay men, and non-Malay men and women, to locate the Islamization and Muslim women's narrative in a wider context. It argues that the restrictive effects of Islamization are being felt by Muslim women but are not always articulated in the public space.